The functional, aesthetic and communicative dimensions of the indicative television advertisement (the advertisements of the Ministry of Health on Al-Iraqiya channel as a model) (Journal of the College of Basic Education, 2022)
Undoubtedly, television advertising has occupied large areas during the broadcast of various television programmes, and the demand for promoting various trends has increased greatly, whether they are commercial with the aim of profit or mobilization and guidance aimed at public interest after the technical and technological development that took place in recent years, and other means could not From underestimating the importance of this advertising medium because it has more credibility than other means, and because it combines sound, image, movement, and various visual and audio effects that appear as if the thing was real, and because it is art and a message directed from a sender to a receiver. The receiver may be young people of both sexes or an old person in The age or young children through a message with an integrated functional and aesthetic design and production that reaches the family as a whole. It has been chosen by governmental organizations to communicate with the public at all levels, including the Ministry of Health. It has taken television first and television advertising secondly as a means of guidance and broadcasting preventive, control and curative messages against most diseases and dangerous health issues. And because the indicative (health) advertisement carries a fateful message, it must be known whether this advertisement is developed It is convincing, just like other types of advertisements that aim for profit only, and accordingly, the subject of our research revolves around (the functional, aesthetic and communicative dimensions in the health indicative television advertisement).